2012
DOI: 10.1007/s13595-012-0190-7
|View full text |Cite
|
Sign up to set email alerts
|

Paternal and maternal effects on the response of seed germination to high temperatures in Eucalyptus globulus

Abstract: & Context High temperature stress in nurseries germinating Eucalyptus globulus seed is an important problem affecting germination synchrony and rate. Where there is a risk of hightemperature stress, then the choice of female parent may be important. This issue is particularly relevant to the production of full-sib families from mass-supplementary pollination where there may be opportunities for seed producers to manipulate the directionality of the crossing done in seed orchards.& Aims This study aimed to quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…The data were summarised into four response traits for each experimental unit of 50 seeds, two measuring proportions and two measuring rates as detailed in Rix et al (2012a;2012b). The proportional data included germination proportion (the proportion of seeds sown that germinated-Germ/Sown) and the proportion of germinated seeds that developed into normal seedlings (Normals/Germ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The data were summarised into four response traits for each experimental unit of 50 seeds, two measuring proportions and two measuring rates as detailed in Rix et al (2012a;2012b). The proportional data included germination proportion (the proportion of seeds sown that germinated-Germ/Sown) and the proportion of germinated seeds that developed into normal seedlings (Normals/Germ).…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, the crossing design does not allow the cause of the maternal genotype influence on seed germination traits to be determined. However, in a study of reciprocal crosses of E. globulus, Rix et al (2012b) showed that both the male and female genotype may affect various aspects of seed germination and early seedling development, independent of seed size, but the response to high temperature stress was more influenced by the maternal than paternal parent.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations